On Modelling of Maximum Electromagnetic Field in Electrically Large Enclosures - Chen, Dan; Hu, Peng; Zhou, Zhongyuan; Zhou, Xiang; Zhai, Shouyang; Chen, Yan (Measurement Science Review, 2022)
The maximum electromagnetic field formed in the electrically large enclosures for a given input power has always been the focus of electromagnetic compatibility issues such as radiation sensitivity and shielding effectiveness. To model the maximums in a simple manner, the electrically large enclosure can be regarded as a reverberation chamber (RC), thus the generalized extreme value (GEV) theory based framework is used for both undermoded and overmoded frequencies. Since the mechanical stirrer is not easy to be installed like that for RC, frequency stirring and mechanical stirring related configurations are discussed, and the corresponding results have confirmed the validity of frequency stirring with the estimate of the parameters in GEV distribution. As for the maximum field, a comparison has been made between GEV distribution and IEC 61000-4-21, and the corresponding results have also highlighted that the maximum field can be assessed by frequency stirring configuration, and by GEV distribution with a desired confidence.